Long-term HIV and tuberculosis outcomes in co-infected patients with treatment limiting severe cutaneous adverse reactions - Veenstra, Simon (Department of Medicine, 2024)
Background Treatment-limiting severe cutaneous adverse reactions (SCAR) occur more commonly amongst persons co-infected with tuberculosis (TB) and advanced HIV. The impact of SCAR on long-term HIV and TB outcomes is unknown. Methods Patients with active TB and/or HIV admitted to Groote Schuur Hospital, Cape Town, South Africa with SCAR between 1/10/2018 and 30/09/2021 were eligible. Clinical and laboratory follow-up data was collected for 6 and 12-month outcomes: mortality, TB and antiretroviral therapy (ART) regimen changes, TB treatment completion, and CD4 count recovery. Results Forty-eight SCAR admissions included: 34, 11, and 3 HIV-associated TB, HIV-only and TB-only patients with 32, 13 and 3 cases of drug reaction with eosinophilia and systemic symptoms, StevensJohnson syndrome/toxic epidermal necrolysis and generalised bullous fixed drug eruption respectively. Nine (19%), all HIV-positive, were deceased at 12-months, and 12 (25%) were lost to all care levels. Amongst TB-SCAR patients, seven (21%) were discharged on all four first-line anti-TB drugs (FLTD), while 12 (33%) had discharge regimens with no FLTDs; 24/37 (65%) completed TB treatment. Amongst HIV-SCAR patients, 10/31 (32%) changed ART regimen. If retained in care (24/36), median (IQR) CD4 counts increased by 12-months post-SCAR (115 (62-175) vs. 319 (134-439) cells/uL). Conclusion SCAR admission amongst patients with HIV-associated TB results in substantial mortality, and considerable treatment complexity. However, if retained in care, TB regimens are successfully completed, and immune recovery is good despite SCAR.